2011
DOI: 10.2460/javma.238.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral transmucosal and intravenous administration of buprenorphine before surgery for postoperative analgesia in dogs undergoing ovariohysterectomy

Abstract: Buprenorphine (HOTM) given immediately before anesthetic induction can be an alternative for postoperative pain management in dogs undergoing ovariohysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 32 publications
3
48
0
2
Order By: Relevance
“…Levetiracetam was well tolerated in this study with no obvious signs of gastrointestinal discomfort or other physiologic changes, and only a brief period of very mild, transient sedation at or near the time of the peak serum levetiracetam concentration was observed. Sedation scoring was modified from a previously reported system based on the DIVAS assessment scale 34. Although the dogs in this study were very consistent in the timing and degree of sedative changes observed, use of a nonvalidated sedation scoring system is considered a limitation in objective assessment of the adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Levetiracetam was well tolerated in this study with no obvious signs of gastrointestinal discomfort or other physiologic changes, and only a brief period of very mild, transient sedation at or near the time of the peak serum levetiracetam concentration was observed. Sedation scoring was modified from a previously reported system based on the DIVAS assessment scale 34. Although the dogs in this study were very consistent in the timing and degree of sedative changes observed, use of a nonvalidated sedation scoring system is considered a limitation in objective assessment of the adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the same research group compared perioperative analgesia provided by buprenorphine OTM or intravenously (IV) after ovariohysterectomy in a small number of dogs, and reported buprenorphine 120 µg/kg OTM to provide a long duration of analgesia of up to 24 hours (Ko and others 2011). It was found that 20 µg/kg OTM or IV provided approximately six hours of analgesia, although the quality of analgesia provided by the 20 µg/kg OTM was poorer than 20 µg/kg IV.…”
Section: Options For Medium-term Opioid Analgesia In Discharged Dogsmentioning
confidence: 99%
“…All dogs were assessed for signs of pain on the basis of modified criteria adopted from 2 pain scoring systems: the DIVAS for soft tissue surgery 21,22 and the MPS developed for stifle joint arthrotomy. 16 Signs of pain were assessed in the following sequence: dogs were observed undisturbed, and signs of pain were assessed from outside of the cage or run; dogs were approached and spoken to, and behavior suggestive of pain was assessed; heart rate, respiratory rate, and blood pressure (measured with a Doppler ultrasound monitor) were assessed; and finally the stifle joint that had undergone surgery was palpated with a palpometer.…”
Section: Methodsmentioning
confidence: 99%
“…16 Signs of pain were assessed in the following sequence: dogs were observed undisturbed, and signs of pain were assessed from outside of the cage or run; dogs were approached and spoken to, and behavior suggestive of pain was assessed; heart rate, respiratory rate, and blood pressure (measured with a Doppler ultrasound monitor) were assessed; and finally the stifle joint that had undergone surgery was palpated with a palpometer. [22][23][24] The general impression of pain consisted of a mean behavioral pain score (undisturbed behaviors and interactive behaviors, including the palpometer use) and a mean objective pain score (increase in heart rate, respiratory rate and systolic arterial blood pressure; Appendix 1). All dogs were continuously monitored visually for the first 4 hours following extubation.…”
Section: Methodsmentioning
confidence: 99%